Instilling Islamic Educational Values Through Madurese Local Cultural Habituation - Nurul Zainab; Abdul Haris (MUSLIM HERITAGE, 2025)
This study aims to explore (1) how State Primary School Patereman 2 utilizes local culture as a medium to instill Islamic educational values, and (2) how the process of internalizing Islamic values occurs through Madurese local cultural habituation. Using a qualitative case study approach, the research involved religious teachers, community religious leaders, students participating in kompolan activities, and parents. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the pattern-matching technique with methodological and source triangulation for validity. The findings reveal that kompolan, a distinctive Madurese religious cultural practice, effectively serves as a vehicle for the internalization of Islamic values among students. The process of habituation creates repeated interactions between learners and the local religious environment, enabling the formation of a religious habitus as explained by Bourdieu’s theory of habitus, capital, and field. This study contributes to the understanding of how ethnopedagogical practices grounded in local culture can strengthen Islamic character education in elementary schools. Abstrak Penelitian ini bertujuan untuk mengeksplorasi (1) bagaimana SD Negeri Patereman 2 memanfaatkan budaya lokal sebagai media penanaman nilai-nilai pendidikan Islam, dan (2) bagaimana proses internalisasi nilai-nilai Islam berlangsung melalui habituasi budaya lokal Madura. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian meliputi guru pendidikan agama Islam, tokoh agama, siswa yang mengikuti kegiatan kompolan, dan orang tua siswa. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi, kemudian dianalisis dengan teknik pattern matching serta triangulasi metode dan sumber untuk menguji validitas data. Hasil penelitian menunjukkan bahwa kompolan, sebagai praktik budaya religius khas masyarakat Madura, terbukti efektif menjadi sarana internalisasi nilai-nilai Islam pada siswa. Proses habituasi menciptakan interaksi berulang antara peserta didik dan lingkungan religius lokal, sehingga terbentuk habitus religius sebagaimana dijelaskan oleh teori Bourdieu tentang habitus, modal, dan ranah. Penelitian ini memberikan kontribusi terhadap pemahaman tentang bagaimana praktik etnopedagogis berbasis budaya lokal dapat memperkuat pendidikan karakter Islam di sekolah dasar.